DEVELOPMENT OF THE ENTREPRISE OF ENTERPRISE CAPITALIZATION STRATEGY - Мельник, Оксана (Socio-economic relations in the digital society, 2019)
In this scientific article, the substantive specificity of the strategy of capitalization of enterprises is defined taking into account the peculiarities of the development of the modern business environment, which directly affects the target processes of capital formation, and therefore their results. As a result of the critical analysis of scientific approaches to strategy definition, the expediency of expanding a threefold understanding of strategy as an interconnection of «strategic context — strategic process — content of strategy» with such a structural element as «strategic orientations» is actualized. The updating of strategic orientations as an element of the invariant strategy structure is conditioned by the fact that in modern conditions the chain of capital formation processes goes beyond the spatial boundaries of the enterprise and expands the space of the business environment, which is presented as a set of development opportunities. Under post-industrial conditions, the results of capitalization are determined by the ability of enterprises to transform the external environment into resources of functioning and business development, which in the processes of productive use ensure the formation of flows of value. Such a substantive statement of the problem actualizes the expediency of managerial focusing on strategic orientations that determine the type of behavior of the enterprise, which directly determines the resultant component of capital formation processes. The implementation of the extended invariant strategy structure in the author’s logic of understanding the enterprise capitalization has made it possible to outline a number of topical issues that are promising from the point of view of further studies of enterprise capitalization. Given the priority of the influence of intangible forms of capital on the results of capitalization, issues related to the quality of capital formation processes in the incorporated plane, as well as assessing their impact on the value of the fundamental capitalization of the enterprise, which is measured by value criteria, become relevant.